Sadar Pilah Sampah Dengan Konsep 4R (Reduce, Reuse, Recycle, Replace) Di Desa Gedongarum, Kanor, Bojonegoro - Yunik'ati Yunik'ati; Rio Miftakhul Imam; Febri Hariyadi; Ismi Choirotin (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Household waste is becoming a common problem in our society. The consumptive lifestyle that is not supported  by a good awareness of waste management resulting in increased waste volume. It  will  give a bad impact on the environment. This community service activity was aimed to provide solutions to waste problems in  Gedongarum Village. The programs arranged were: waste sorting through socialization and training activity of 4R concept (Reduce, Reuse, Recycle and Replace), and manufacturing of waste sorting facilities.  The results of the evaluation showed that the awareness of the community to the importance of waste sorting and processing increased by 58.7% and the knowledge on waste management, increased by 76.05%. The effectiveness of the program's success amounted to 71.7%, while 86,9% of the respondents support the activities to be sustainable.